IMPROVING STUDENTS’ VOCABULARY MASTERY THROUGH FLASHCARD MEDIA AT THE EIGHT GRADE - Agustin, Milan Dwi (Critical Review of English-Arabic World Journal, 2024)
The problem of this study was the students’ vocabulary mastery was still low. The research objective of the research to find out whether flashcards can improve students’ vocabulary mastery at the eight grade of Mts. Raudlatus Syabab. The research used Classroom Action Research (CAR). The research design was a collaborative classroom action research. The participants of this research were the students 8C of Mts. Raudlatus Syabab, which consists of 26 students. The research was carried out in two cycle, which consisted of planning, implementing, observing, and reflecting. Data collecting techniques used in this research were preliminary-test and post- test, observation sheet and interview. This research used content validity, which involved the English teacher, the researcher conducted two tests for the students and determined the criteria of success. The minimum score determined by the researcher to reach the criteria of success is 75 was equal to or higher than 65% of total students in this research. The result of this research showed that: the students could not pronounce the word correctly and fluently with different subject matter and treatment in cycle 2, and the average students score is 73%. It can be concluded that flashcards media can improve students’ vocabulary mastery.The problem of this study was the students’ vocabulary mastery was still low. The research objective of the research to find out whether flashcards can improve students’ vocabulary mastery at the eight grade of Mts. Raudlatus Syabab. The research used Classroom Action Research (CAR). The researchdesign was a collaborative classroom action research. The participants of this research were the students 8C of Mts. Raudlatus Syabab, which consists of 26 students. The research was carried out in two cycle, which consisted of planning, implementing, observing, and reflecting. Data collecting techniques used in this research were preliminary-test and post-test, observation sheet and interview. This research used content validity, which involved the English teacher, the researcher conducted two tests for the students and determined the criteria of success. The minimum score determined by the researcher to reach the criteria of success is 75 was equal to or higher than 65% of total students in this research. The result of this research showed that: the students could not pronounce the word correctly and fluently with different subject matter and treatment in cycle 2, and the average students score is 73%. It can be concluded that flashcards media can improve students’ vocabulary mastery.